Relevance of the ancestry for the variability of the Drug-Metabolizing Enzymes CYP2C9, CYP2C19 and CYP2D6 polymorphisms in a multiethnic Costa Rican population - Céspedes-Garro, Carolina (2016)
CYP2C9, CYP2C19 and CYP2D6 metabolize around 40% of drugs and their genes vary across populations. The Costa Rican population has a trihybrid ancestry and its key geographic location turns it into a suitable scenario to evaluate interethnic differences across populations. This study aims to describe the diversity of CYP2C9, CYP2C19 and CYP2D6 polymorphisms in Costa Rican populations in the context of their ancestry. A total of 448 healthy individuals were included in the study: Bribri (n= 47), Cabécar (n= 27), Maleku (n= 16), Guaymí (n= 30), Huetar (n= 48), Chorotega (n= 41), Admixed/Mestizos from the Central Valley/Guanacaste (n= 189), and Afro-Caribbeans (n= 50) from Limón. CYP2C9 (alleles *2, *3, *6) and CYP2C19 (*2, *3, *4, *5, *17) genotypes were determined by Real-Time PCR. African, European and Native American ancestry were inferred using 87 ancestry informative markers. The frequency of the decreased activity allele CYP2C9*2 is lower in the self-reported Amerindian groups compared to the admixed population, and the highest frequencies of CYP2C19*2 (null activity) and the CYP2C19*17 (increased activity) were found in the self-reported Afro-Caribbean population. Moreover, a frequency of 0.7 % CYP2C9 gPMs in the Admixed population and a variable frequency of CYP2C19 gUMs (0.0-32.6 %, more prevalent in Afro-Caribbeans) in Costa Rican populations, was found. Finally, the following alleles were positively correlated with genomic African ancestry and negatively correlated with genomic Native American ancestry: CYP2D6*5 (null activity), CYP2D6*17 (decreased activity), CYP2D6*29 (decreased activity) and CYP2C19*17 (increased activity). No correlation for CYP2C9 polymorphisms and genomic ancestry was found. Further studies assessing the CYP2C9 and CYP2C19 sequence in these populations, preferentially by sequencing these genes, are warranted.